Pengaruh Motivasi Kerja, Gaya Kepemimpinan dan Pengalaman Kerja Terhadap Kinerja Karyawan PT ELKAU - Sukri Sukri; Mukti Rahardjo (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This study aims to analyze and prove work, work experience and leadership styles on employee work simultaneously or partially. This study used a survey using a questionnaire to 96 respondents, PT ELKAU staff. Sample selection is based on random sampling everywhere Every participant has the same opportunity to take samples. The results of this study prove that work motivation, work experience and leadership styles simultaneously influence employee performance. Partially, work experience increases performance with a significant level of 0,000, work motivation while positive performance on performance is significant level of 0.017 and leadership style increases positive performance on work performance with a significant level of 0,000. Further research is expected to add other factors that can improve job performance.